Collusive practices in public procurement and the effects of the antitrust compliance and leniency program - García Coso, Emiliano (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This article focuses on the analysis of collusive practices in public procurement andthe application of competition rules to protect the affected public interest, both in the European marketand, especially, in the Spanish market. Bidding companies in public procurement may engage in secretcartels or “bid rigging,” which are difficult for contracting authorities and competition authorities to detect.Despite the reforms introduced in Spanish legislation to coordinate between contracting authoritiesand competition authorities and the adoption of a prohibition on contracting as a legal consequence, bidrigging continues to occur. Therefore, this paper analyzes the potential benefits that can be achievedby introducing an ex ante competition law compliance program for bidding companies, or “antitrustcompliance,” which not only protects the public interest but also the bidding companies themselves andtheir responsible executives from the administrative sanctions associated with engaging in collusive practices. Finally, the use of leniency programs is addressed as a tool that facilitates investigations intocollusive practices in public procurement, but which raises certain concerns for applicants due to itsimpact on private actions seeking damages.
Keywords: Collusive practices; bid rigging; public procurement; competition law compliance program; leniency program